Assessment of inappropriate use of antibiotics and contributing factors in Awi Administrative Zone, Northwestern Amhara regional State, Ethiopia - Belsti Atnkut; Atalaye Nigussie; Bekele Gebreamanule; Bulti Kumera; Tess Astatkie (New Microbes and New Infections)
Objectives: Antibiotic misuse is regarded as the single most significant factor contributing to resistance. Thus, this study aimed to evaluate the prevalence and risk variables linked to the inappropriate use of antibiotics in urban and rural districts of the Awi administrative zone community. Methods: A total of 1194 rural and urban families, including individuals of various ages and genders from the study area were selected by a multistage stratified random sampling method for a comparative cross-sectional study conducted between December 2022 and June 2023. SPSS version 26 was used to analyze the gathered data. Descriptive statistics and logistic regression analysis methods were used to identify the variables linked to the incorrect use of antibiotics. The adjusted odds ratio was used to calculate the statistical significance of the correlation at a significance level of 5 %. Results: The findings revealed that, in urban and rural regions, 57.5 % and 69.5 % of the households used unsafe antibiotic practices. The logistic regression analysis showed a significant relationship between the inappropriate use of antibiotics and the household head's age, marital status, family size, monthly income, occupation, educational attainment, place of residence, knowledge of antibiotics, and practice of using antibiotics. Conclusion: The study area has inappropriate antibiotic use, with statistically significant differences between urban and rural communities. Extensive educational (knowledge and practice) interventions are required to enhance the appropriate use of antibiotics. To guarantee that antibiotics are dispensed correctly and that the right information is provided regarding how the antibiotic functions and should be used, authorized entities should strengthen their regulatory enforcement at pharmacies.